2015
DOI: 10.1038/ctg.2015.60
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Best Way to Identify Malignant Transformation Within Pancreatic IPMN: A Systematic Review and Meta-Analyses

Abstract: Objectives:Pancreatic intraductal papillary mucinous neoplasias (IPMNs) represent 25% of all cystic neoplasms and are precursor lesions for pancreatic ductal adenocarcinoma. This study aims to identify the best imaging modality for detecting malignant transformation in IPMN, the sensitivity and specificity of risk features on imaging, and the usefulness of tumor markers in serum and cyst fluid to predict malignancy in IPMN.Methods:Databases were searched from November 2006 to March 2014. Pooled sensitivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 72 publications
0
35
0
Order By: Relevance
“…Revisions to the Fukuoka guidelines recommend that low‐risk BD‐IPMN should be followed up by CT, MRI, and/or EUS at appropriate intervals, based on the size of each initial cyst. The main concern is the development of malignancy in the cyst and many studies have reported the natural history of malignant progression of low‐risk BD‐IPMN . However, the majority of incidental IPMN in clinical setting are small in size and lack currently defined high‐risk features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Revisions to the Fukuoka guidelines recommend that low‐risk BD‐IPMN should be followed up by CT, MRI, and/or EUS at appropriate intervals, based on the size of each initial cyst. The main concern is the development of malignancy in the cyst and many studies have reported the natural history of malignant progression of low‐risk BD‐IPMN . However, the majority of incidental IPMN in clinical setting are small in size and lack currently defined high‐risk features.…”
Section: Discussionmentioning
confidence: 99%
“…It is also essential to identify factors associated with disease progression to malignancy in BD‐IPMN. Several studies have reported that those factors included cystic features (cyst size, the presence of a mural nodule, MPD dilatation, and growth rate in size) and patient's factors (symptoms, diabetes mellitus, smoking, or obesity). However, few data are available on risk factors of imaging progression in low‐risk BD‐IPMN .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our viewpoint was also agreed by many other researchers, who reported that serum CA 19–9 was a useful non-invasive tool for distinguishing malignant IPMNs, and should be taken into account in the decision to offer surgery. [ 15,17,36 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 23,40 ] The pooled sensitivity and specificity of 18-FDG PET were 0.968 (95% CI: 0.90–0.99) and 0.91(0.81–0.99). [ 36 ] As 18-FDG PET is not routinely performed for its high cost and radiation, the decision of whether to do a surgery or not remains challenging. [ 41 ] Studies of molecular markers were also reported recently.…”
Section: Discussionmentioning
confidence: 99%